Granulated Biochar–MMT–Zn/Al LDH Composite as a Durable Adsorbent for Column Applications - Rahmat Fadhilah; Destria Enjelika; Dedy Anwar; Sudibyo Sudibyo; Asnan Rinovian; Hana Safitri; Lia Nurbanillah Fujianti; Dodi Devitriano; Hutwan Syarifuddin; Anis Tatik Maryani; Yudha Gusti Wibowo (Universitas Diponegoro, 2026)
Granular adsorbents are essential for fixed-bed column systems because they reduce the pressure drop and minimize the material loss commonly associated with powdered adsorbents. However, transforming powdered materials into mechanically stable granules without compromising their structural integrity remains a significant challenge. In this study, a granulated composite consisting of biochar, montmorillonite (MMT), and Zn/Al layered double hydroxide (LDH) was developed as a potential adsorbent for column application. Biochar derived from Avicennia marina biomass was combined with MMT and Zn/Al LDH to produce a composite material, which was subsequently granulated using bentonite, tapioca starch, and polyvinyl alcohol (PVA) as binding agents. The resulting granules (0.5–1.5 cm in diameter) were evaluated for mechanical durability under static water immersion and dynamic water flow conditions. The results indicate that the binder composition strongly influences granule stability. Granules prepared without PVA rapidly disintegrated in aqueous environments, whereas the inclusion of PVA significantly improved structural durability. The optimized formulation exhibited durability of up to 8208 min under static conditions and maintained its structural integrity under continuous water flow. These results demonstrate the potential of Biochar–MMT–Zn/Al LDH granules as durable adsorbents for fixed-bed column water treatment systems